Autism and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The prevalence of autistic spectrum disorder (ASD) in children (2-18 years of age) with epilepsy was evaluated at a Tertiary Care Epilepsy Clinic at the Hospital for Sick Children, Toronto, Canada